FM as a business enabler: Solutions for managing the built environment - Madan, Sunil, Madan; Drogemuller, Robin; Mitchell, John; Schevers, Hans; Tonelli, Marcello; Clark, Selwyn; Frowd, Andrew; Ballesty, Stephen; Ferrara, Nicholas; Morris, Jason; Shah, Ankit; Akhurst, Paul; et al. (CRC for Construction Innovation, 2007)
FM as a business enabler Sydney Opera House is recognised throughout the world as a building icon of 20th century architecture. The Cooperative Research Centre (CRC) for Construction Innovation and the Australian Government’s FM Action Agenda chose this iconic symbol as the focus of its Facilities Management (FM) Exemplar Project and partnered with industry, government and research to develop innovative strategies across three research themes. 1. Digital modelling — developing a building information model capable of integrating information from disparate software systems and hard copy, and combining this with a spatial 3D computer-aided design (CAD)/geographic information system (GIS) platform. This model offers a visual representation of the building and its component elements in 3D, and provides comprehensive information on each element. 2. Services procurement — developed a multi-criteria performance-based procurement framework for FM service delivery 3. Performance benchmarking — developed an FM benchmarking framework that enables facilities/organisations to determine key performance indicators (KPIs) to identify best practice and improvement strategies. This project provides a broad range of practical input from client, consultants and service providers. The project’s outcomes will in turn support the industry’s FM Action Agenda. The innovative methods delivered by this project should be implemented across the FM industry at the strategic, management and operational levels. Further research on the FM Exemplar Project outputs would assist in developing a broader application of the integrated FM solution to other facility types and benefit the FM industry and the community at large.